The Functional Psychotherapy Approach: A Process-Outcome Multiple Case Study - Rocco, Diego; Rizzi, Luca; Dell’Arciprete, Gaia; Perrella, Raffaella (Frontiers in Psychology, 2022)
Objective: The present work aims to conduct the first naturalistic empirical investigation of the process and outcome assessment of functional psychotherapy (FP) treatment. The FP model of psychotherapy is rooted in psychoanalysis and integrates the verbal communication approach founded on transference and countertransference dynamics with the analysis of bodily processes. Method: The study sample included ten patients recruited on a voluntary basis and treated by clinicians in their private practices. Each patient received FP with an average duration of 40 h (min 35 and max 42). Therapies had weekly sessions, were audio-recorded with the patient’s written consent, and lasted for an average of 10 months (min 9 and max 12). Outcome and process tools included the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) and the Luborsky’s the Core Conflictual Relationship Theme (CCRT), used to assess therapeutic benefit, and the Metacognition Assessment Scale (MAS) and the Italian Discourse Attributes Analysis Program (IDAAP) system, used to evaluate therapeutic benefit and process. The MMPI-2 was used also in the follow-up assessment. Results: Results show that FP had a positive therapeutic outcome on the patients assessed in this study, and that the therapeutic benefits were maintained over time. Some specific features of the FP approach were found to contribute more than others to the observed therapeutic benefits. Conclusion: The current investigation constitutes a first step toward assessment of the therapeutic effectiveness of FP. Future developments should apply the methodology to a larger sample, possibly introducing different methodologies to enable detection of specific bodily oriented processes and techniques.